Economic contents and essence of enterprise risk (Journal of Economic Research & Business Administration, 2016)
In article is considered problems of threats and existence of enterprise risks. Implementation of business in its any kind is connected with risk which it is accepted to call economic, or enterprise. In article attempt to find out sources and the reasons of such risk and a form of its manifesta-tion further to understand methods of an assessment of risk and ways of its prevention is made.
Keywords: business activity; uncertainty; enterprise risk; probability of losses.